2004
DOI: 10.4319/lo.2004.49.3.0862
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐nitrogen coupling and algal‐bacterial interactions during an experimental bloom: Modeling a 13C tracer experiment

Abstract: We tracked flows of carbon and nitrogen during an experimental phytoplankton bloom in a natural estuarine assemblage in Randers Fjord, Denmark. We used 13 C-labeled dissolved inorganic carbon to trace the transfer of carbon from phytoplankton to bacteria. Ecosystem development was followed over a period of 9 d through changes in the stocks of inorganic nutrients, pigments, particulate organic carbon and nitrogen, dissolved organic carbon (DOC), and algal and bacterial polar-lipid-derived fatty acids (PLFA). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 56 publications
(107 reference statements)
4
87
1
1
Order By: Relevance
“…Mykelstad (1988) showed that when nitrate and phosphate are depleted, diatoms (which are abundant in the North Sea) produce more glucan (5carbohydrates) and therefore continue consuming DIC, whereas they stop synthesizing proteins (rich in N and P atoms), leading to an increase of the cellular C : N ratio. Moreover, van den Meersche et al (2004) examined the different phases of a phytoplankton bloom in the Randers Fjord, Denmark. These authors showed that during the first period of the bloom, nutrients were replete, and an algal bloom was observed, with carbon and nitrogen uptake occurring at a constant Redfield ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Mykelstad (1988) showed that when nitrate and phosphate are depleted, diatoms (which are abundant in the North Sea) produce more glucan (5carbohydrates) and therefore continue consuming DIC, whereas they stop synthesizing proteins (rich in N and P atoms), leading to an increase of the cellular C : N ratio. Moreover, van den Meersche et al (2004) examined the different phases of a phytoplankton bloom in the Randers Fjord, Denmark. These authors showed that during the first period of the bloom, nutrients were replete, and an algal bloom was observed, with carbon and nitrogen uptake occurring at a constant Redfield ratio.…”
Section: Resultsmentioning
confidence: 99%
“…VAN DEN MEERSCHER et al (2009) showed depleted bacterial signatures, however they were similar to DOC and POC and clearly different from algae. This allowed them to propose that bacteria could be used as proxy for allochthonous carbon, whereas algae would represent autochthonous organic matter sources (Figure 5b).…”
Section: C-tcmentioning
confidence: 87%
“…For comparison of organic matter quality between treatments, the geometric mean of the ratios of POC to POP (POC:POP mean ) and DOC to DOP (DOC:DOP mean ) was calculated for the period from nutrient depletion onward until the last day of the bloom period. With regard to the accumulation of dissolved organic components and the elemental composition of organic matter, the onset of nutrient depletion is generally a cardinal time point in bloom situations, as it may trigger the exudation and accumulation of dissolved carbon-rich material (Norrman et al 1995;Thingstad et al 1997;Van den Meersche et al 2004). This often leads to strong deviations in organic matter stoichiometry and may hence affect food web dynamics.…”
Section: Calculationsmentioning
confidence: 99%